Are Clinicians Communicating Adequately with Radiologists Through Radiological Requisition? A Clinical Audit Assessing Current Local Practice - Zubair Janan Orakzai, Tabassum Begum, Shamoona Rashid, Nasreen Akhtar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: To prevent controversy, the request forms were selected to use a method of convenience sampling and also included forms from both inpatient and outpatient different department. The aim of this study whether the different request forms that were submitted to the radiological department and notice that the patients having complete information in each form of different department of radiology. Study design: This was retrospective and descriptive study. The study was carried out at the department of Radiology, MTI Mardan Medical Complex, Mardan for six months duration from May 2022 to October 2022. Methods: The total participants request form were 300 which distribute, 85 forms in CT (computated tomography), 105 forms in MRI (magnetic resonance imaging) and 110 forms in US (ultrasound image). The completeness of the data entered by the doctors was examined on the forms to avoid bias. Results: Our audit information indicate that to analysed 300 request forms were filled out just the name of patients as well as part of examination. The different category of request form included name, age, diagnosis diseases, relevant history and Dr. Name or contact number. Conclusion: The referring doctors managed to fail to fully and precisely fill out all of the disciplines. To recognize this system and communicate about how it may be done better, we suggest having discussions with radiologists and doctors from different departments. Keywords: Radiologists, Radiology request form, Adequate.